The moral education in the school: revisions and alternatives based on the contributions of Psychology - Lepre, Rita Melissa [UNESP] (Univ Federal Santa Maria, 2019)
The goal of this article is to present a review of Moral Education in the Brazilian school, based on official documents and propose alternatives for teaching praxis in this area of knowledge, based on the studies of Psychology and Genetic Epistemology. For that, we carried out an analytical research on the revision of Moral Education in Brazil and on the need to rescue this theme in the face of the new contemporary challenges regarding the construction of moral values, from a Piagetian perspective. The results demonstrate the urgent need to retake the issue of education in values in educational guidelines and ratifies the importance of the interdisciplinary dialogue between Psychology and Education aimed at this end.
Keywords: Moral Education; School; Teaching Praxis